Identifying as a Librarian: When and If LIS Graduates in Non - Library Roles Use the Title “Librarian” - Fraser-Arnott, Melissa (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2018)
This poster addresses how library and information science (LIS) graduates who work in non - library roles label themselves. The LIS community as the profession is undergoing a time of transition. Given the changing nature of the work that is being performed by LIS graduates both inside and outside of libraries, the timing is appropriate to explore how practitioners choose to label themselves as professionals. LIS graduates working in non - library roles where selected as the target population of this study because their w ork provides them with myriad possibilities for self- labelling. Participants exhibited four response patterns which are described and discussed.